The Slovak Republic’s view of energy security as a theoretical problem - Juza Peter (Право и государство, 2016)
Nowadays the importance of energy security in practice is constantly increasing due to the necessity to follow this issue from both - theoretical and practical points of view. The article analyzes relation between energy security and a possible war, which would concern energy resources of a particular country. The article contains specific analysis of the possibility to maintain energy security of the Slovak Republic, activities of the European Union and the position of the Russian Federation in the field of energetics as well as the prospects for development of mutual energy affairs and ratio of their energy interdependence in the future.
Keywords: energy security; energy interdependence; еnergy affairs; international affairs; Research Subject Categories::LAW/JURISPRUDENCE